Carbon nanostructures: formation and evolution in the laboratory and the ISM - Gover, Rachel K.E. (2016)
The chemistry of large carbon-containing molecules in space is widely researched with notable advances including understanding of the aromatic infrared emission features in terms of their general origin in polycyclic aromatic hydrocarbon (PAH) molecules, identification of the fullerenes C60 and C70 as the largest molecules detected in the interstellar medium, and knowledge of the structure and composition of various solid-state interstellar grains. However, there remain major challenges. The work described in this Thesis addresses some longstanding, unanswered questions in astrochemistry, such as the origin of variation in the profiles of the aromatic infrared bands, the route to formation of C60, and the role of astrophysical grains in the reactions of carbon-containing species. This research was carried out using a range of laboratory and computational techniques, in combination with astronomical data, yielding new results that can be compared with existing work to find solutions to these problems. The varying profile of the 11.2 μm aromatic infrared emission band within two objects, NGC 7023 and the Red Rectangle, is investigated. The feature’s changing spectral shape, which depends on the position within the object, is interpreted in terms of variation in the distribution of molecular masses of the PAHs that give rise to the feature. This was achieved using a model that fits astronomical data which was obtained with the instrument MICHELLE on the UKIRT telescope in Hawaii and the Spitzer satellite observatory. Based on the calculated emission features of four neutral PAHs that are taken to represent ‘low-mass’ (fewer than 50 C atoms) or ‘high-mass’ (more than 50 C atoms), it is found that, with increasing distance from the star, there is an increase in the proportion of low-mass PAHs in NGC 7023, in good agreement with less specific previous studies that have been carried out using other approaches. The modelling results for the Red Rectangle indicate that the mass distribution does not change significantly with offset, although evidence from other sources appears in part to contradict this conclusion. A laboratory investigation is detailed in which formation of C60 from PAH precursors is explored. Transmission electron microscopy (TEM) and matrix-assisted laser desorption/ionisation time-of-flight mass spectrometry (MALDI-TOF MS) are used to irradiate, using the electron beam (e-beam) in TEM and the UV laser in MALDI-TOF MS, samples of PAH molecules and to monitor the products of any resulting transformations within the samples. It is found that under both e-beam and UV irradiation, PAH molecules lose one or more H atoms and form larger PAH 'oligomers’. Based on the MALDI-TOF MS results, specific chemical structures of these oligomers are proposed, and it is found that the precursor molecules coronene and perylene give rise to formation of C60. A mechanism is given for this process, in which an oligomer containing 60 carbon atoms or more is formed, and then ‘shrinks’ via loss of H atoms, C-C bond formation, and Stone-Wales rearrangements. Important structural features required for these mechanisms, namely the presence of ‘bay’ and 'fjord’ carbon edge sites, are discussed in an astrophysical context. An experimental methodology was designed and implemented to use TEM and MALDI-TOF MS in conjunction with each other, in which a specific area of a PAH sample is viewed using low-dose TEM, is then irradiated using the UV laser in MALDI-TOF MS, and finally is viewed a second time using TEM to observe the effects of the UV irradiation. Experiments were carried out to investigate reactions of acetylene and CO in the presence of astrophysically relevant grains. It was found that CO undergoes a disproportionation reaction over olivine grains, forming gaseous CO2 and depositing solid-state carbon on the grain surface; this has implications for the formation of other carbonaceous species such as PAHs and even carbon nanotubes. The formation of PAHs from acetylene gas over grains of SiC is reported, in addition to the inhibiting impact of CO when mixed with acetylene. In one experiment olivine samples were irradiated by the e-beam in TEM, and decomposition of the olivine structure was seen to occur, resulting in the formation of metallic nanoparticles. This behaviour is discussed in terms of its likely occurrence in astrophysical environments such as the Red Rectangle, and its potential for catalysis that results from reactions of molecules on the metal nanoparticle surface.